PELATIHAN PENGEMBANGAN KONTEN E-LEARNING MENGGUNAKAN GOOGLE CLASSROOM SEBAGAI INOVASI PEMBELAJARAN GURU MATEMATIKA SMP - Suryanti, Sri; Edy, Sarwo; Uchtiawati, Sri (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
The problem that underpins the program to develop e-learning content development using Google Classroom for teachers of SMP Muhammadiyah 4 Kebomas is the fact that the gap between Muhammadiyah schools in Gresik is quite sharp. The purpose of this community service is to improve the competency of teachers in the development of teaching materials using Google Classroom as one of the learning innovations for teachers in SMP Muhammadiyah 4 Kebomas Gresik. The implementation of the program as a realization of problem-solving materialized in periodic and scheduled activities through strengthening the concept of e-learning learning using Google Classroom, followed by the needs Analysis Workshop, e-learning system design Workshop using Google Classroom, e-learning content development Workshop using Google Classroom, Upload the development results to the system LMS In the implementation stage using the Lesson Study steps as many as two cycles. The methods used in the implementation of this activity are by process of discussion, workshop, and practice directly in the classroom. The results of this activity are the growing understanding of teachers about e-learning, Generated e-learning design consisting of the material design of each meeting, discussion activities for students, evaluation tools; Teachers can implement e-learning independently.